DETERMINATION SERVICES AGAINST WORD OF MOUTH THROUGH CUSTOMER SATISFACTION : STUDY ON TRAVEL HAJJ AND UMRAH PT. CAHAYA SUKSES MANDIRI - Dhoni Marwan (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to analyze the effect of service on customer satisfaction, the effect of service on word of mouth, the effect of trust satisfaction on word of mouth and to analyze the indirect effect of service on word of mouth through customer satisfaction. Travel Hajj and Umrah PT. Cahaya Sukses Mandiri. The approach used in this research is an associative approach. Data collection techniques used were interviews (Interview), a list of questions (Questionaire) and documentation study. The sampling technique is a non-probability sampling technique. The study population was all of the PT Cahaya Sukses Mandiri Umrah pilgrims from 2019, totaling 63 people. And the sample in this study were 63 people by taking the sample by census. The data analysis technique is the analysis of the path (path analysis). The results showed that service has a positive and significant effect on customer satisfaction, service has a positive and significant effect on Word of mouth, customer satisfaction has a positive and significant effect on Word of mouth , and customer satisfaction acts as a mediator on the effect of service on Word of mouth on Hajj Travel. and Umrah PT. Cahaya Sukses Mandiri . Keywords: Customer Service, Word of Mouth, Customer Satisfaction